LEADER-FOLLOWER FORMATION CONTROL ON QUADROTOR USING VISUAL POSITIONING SYSTEM AND PROPORTIONAL-DERIVATIVE CONTROLLER - LANA ASRI (NIM : 13313001) - RIFQI RAFIFANDI (NIM : 13313013), DEA
Swarm algorithm is a formation algorithm that mimics the behaviour of a group of animals like bees and birds. Leader-follower formation is one of the swarm algorithms where a follower vehicle follows a track that has been set by a leader vehicle. In this research, two quadrotors were used to form a leader-follower formation. In a leader-follower formation, there is a need for a positioning system so that the quadrotors can follow commands within the formation. There are three elements in the design of leader-follower formation control, which are positioning system, quadrotor position tracking, and leader-follower formation algorithm. Visual-based positioning system is used by using QR codes as markers, where images that are produced by the quadrotor vertical camera are used to identify markers. This positioning system has an accuracy of 10 cm. Quadrotor position tracking is performed to test the ability of a quadrotor to follow a certain path, which consists of identification of the movement characteristics of quadrotor, tuning of PD controller parameters using root locus method, and testing of the position tracking. The movement characteristics of the quadrotor on four axes (𝑥+, 𝑥−, 𝑦+, and 𝑦−) resembles a first-order system with time delay. Leader-follower algorithm is designed after the positioning system and quadrotor position tracking is successfully implemented. Leader and follower quadrotors move on the direction of the 𝑥-axis. The leader and follower quadrotors are able to form a leader-follower formation with 300 cm gap on the 𝑥-axis, even though there are points where the gap between the two quadrotors reach 573 cm on the 𝑥-axis.